Let x represent speed of kayak in the still water.
We have been given that a kayaker paddles 2 km upstream in the same time that it takes to paddle 3 km downstream. The average speed of the current is 1 km/h.
Speed of kayak upstream would be speed of kayak in still water minus speed of the current that is .
Speed of kayak downstream would be speed of kayak in still water plus speed of the current that is .
Time taken to travel 2 km upstream would be .
Time taken to travel 3 km upstream would be .
Since both times are equal, so we can equate both expressions as:
Cross multiply:
Therefore, the average speed of Kayak in still water is 5 km per hour.
The required simplified solution of the given expression is 11x -8.
Given that,
To determine the simplified expression that is equivalent to the 3(x-2)+2(4x-1).
The process in mathematics to operate and interpret the function to make the function or expression simple or more understandable is called simplifying and the process is called simplification.
Here,
Given expression,
3(x-2)+2(4x-1)
Applying the distributive law in order to multiply the 3 and 4 in the respective parenthesis.
= 3x - 6 + 8x - 2
= 11x - 8
Thus, the required simplified solution of the given expression is 11x -8.
Learn more about simplification here: brainly.com/question/12501526
#SPJ2
Between 0.5 and 0.6 can be an infinity.
ex:
0.51
0.52
0.517
0.5169889549.......
0.5999999999..........
etc.
(-3x + 20)
(-2x + 55)
Answer: Solution for (-3x+20)+(-2x+55)=180 equation: x= -21
Step-by-step explanation:
Simplifying
(-3x + 20) + (-2x + 55) = 180
Reorder the terms:
(20 + -3x) + (-2x + 55) = 180
Remove parenthesis around (20 + -3x)
20 + -3x + (-2x + 55) = 180
Reorder the terms:
20 + -3x + (55 + -2x) = 180
Remove parenthesis around (55 + -2x)
20 + -3x + 55 + -2x = 180
Reorder the terms:
20 + 55 + -3x + -2x = 180
Combine like terms: 20 + 55 = 75
75 + -3x + -2x = 180
Combine like terms: -3x + -2x = -5x
75 + -5x = 180
Solving
75 + -5x = 180
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-75' to each side of the equation.
75 + -75 + -5x = 180 + -75
Combine like terms: 75 + -75 = 0
0 + -5x = 180 + -75
-5x = 180 + -75
Combine like terms: 180 + -75 = 105
-5x = 105
Divide each side by '-5'.
x = -21
Simplifying
x = -21